ANALISIS KAPASITAS TRAFIK WAP PADA DAERAH URBAN DALAM SISTEM WLL DENGAN TEKNOLOGI DCS 1800 - Wijayapraja, R. Deiny Mardian (Jurnal Teknik Elektro, 2006)
One of the cellular communication form is the data communication beside voicecommunication. Wireless Application Protocol (WAP) is a data communication which hascomplete features. This data/WAP communication might be a service in Wireless Local Loop(WLL) for the busy urban area. For example at Sudirman business area in Jakarta. If thecellular communication users in this area use this service actively it will increase the datacommunication traffic.To analyze the data/WAP communication traffic in urban WLL with DCS 1800technology we may use several analyses from the DCS 1800 itself and some simulation ofurban WLL area. Theyâll give the illustration of the data/WAP communication trafficcapacity and the prediction about availability channel in an urban WLL using DCS 1800technology.There is a case study - the future prediction - which 202 data/WAP channels indemand. DCS 1800 technology could gives 55% of its 350 data/WAP channels while somerecent BTS have to increase 3 to 67 times of their 3 to 82 available data/WAP channels tohandle the case studyâs demand. Recently, the data/WAP communication traffic is about 2%of the total communication traffic. It means that DCS 1800 provides just 21 data/WAPchannels of its 350 total data/WAP channels today.Keywords: cellular, communication, WAP, WLL, urban